Balancing the scales: an attempt to measure the grievances of war victims / Nabeela Siddiqui - Siddiqui, Nabeela (2014)
The whole notion of warfare is of a primordial origin and has developed throughout the epochs from an 'abstract‟ concept to an 'absolute‟ concept. The history of Wars and Warfare are evident to show how they have been subjected to continuous transformation. One way to catalogue warfare is by differentiation between conventional versus unconventional, where conventional warfare involves well-identified, armed forces fighting one another in a relatively open and candid way without weapons of mass destruction. "Unconventional" refers to other types of war which can involve raiding, guerrilla, insurgency, and terrorist tactics or alternatively can include nuclear, chemical, biological warfare or using propaganda with pressure groups etc.